Management of knowledge in SMES on services sector. An empirical approach in Mexico´s state - Escamilla-Salazar, Zugaide; Caldera-González, Diana del Consuelo; Ruiz-Lara, Fortino (Unidad Editorial UPTC, 2020)
The impact that small and medium-sized enterprises (SMEs) have on the development of societies is undeniable, despite the challenges they face in an uncertain and changing world. This environment forces them to be more competitive and one way to achieve this is by planning and controlling what to do and know-how in the organization as part of the integration of knowledge management. The objective of this work is to identify the most significant indicators of the knowledge management factor in SMEs in the service sector in a municipality in the Northern Zone of the State of Mexico. For this purpose, the statistical contingency table technique is used. The main results show that the imitation indicator is significant for the group of female and male entrepreneurs in the sample of this research, which alerts us to the lack of planning for the issue of knowledge management in this kind of companies. Keywords: Knowledge management, Factors, Competitiveness, SME’s, Mexico. JEL Classification: L1, L2, D8 Received: 16/03/2019.  Accepted: 28/04/2020.  Published: 30/06/2020.